STUDY OF VITAMIN B12 DEFICIENCY AND ITS RELATION WITH METFORMIN TREATMENT AMONG DIABETICS IN PRINCE RASHID HOSPITAL - Aljabra, Rabia Jamil; Al-Noimi, Faisal Awad; Batayha, Noor "Mohammad Said" Mustafa; Telfah, Hadeel Aiman; Andrawes, Shireen Tayseer; Alrabbaei, Husban; Abeeleh, Jaafar Abu (European Scientific Journal, ESJ, 2015)
Introduction: Vitamin B12 has important functions in physiology and pathology of human body. It can help against diseases through improving immune system. The role of Its deficiency with metformin treatment is still subjecting to diabetes. Objectives: 1. To investigate the prevalence of Vitamin B12 deficiency among diabetics visiting internal medicine clinics in Prince Rashid Hospital. 2. To explore the association of Vitamin B12 deficiency with metformin treatment among the same sample. Methods and subjects, Study design: A retrospective design was employed to collect data from files of diabetic patients. Study sample: A total of 447 files of diabetic patients were accessed if inclusion criteria were met. Inclusion criteria: Diabetic patient. Vitamin B12 status is mentioned. Metformin treatment is recorded in files of diabetic patients. Data collection: data will be collected for each patient and entered into excel sheet for further analysis. Statistical analysis: SPSS version 20 was used for data analysis. Data was presented as frequency and percentage for numerical variables, whereas the association between variables was tested using Chi- Square test. Significance was tested at alpha level < 0.05. Results: The prevalence of vitamin B12 deficiency was 7.2%. The mean age of study participants was 55.70+10.13 years. Metformin intake was reported by approximately 84% of diabetics. About 76% of participants had cardiac diseases. No significant association was observed between metformin and vitamin B12 deficiency (p=0.269). Conclusion: The prevalence of vitamin B12 deficiency among diabetics was 7.2%. No significant association was observed between treating diabetics with metformin and vitamin B12 deficiency. Recommendation: Lacking the association between treatment of metformin and vitamin B12 deficiency may due to small participants included in other studies, and we recommend to include larger numbers of participants in future studies.